TATA KELOLA TEKNOLOGI INFORMASI UNTUK MENGGALI MANFAAT STRATEGIS TEKNOLOGI INFORMASI BAGI BISNIS - Marcel, Marcel (Teknik dan Ilmu Komputer, 2012)
IT governance describes about how IT can assist organizations to pursue and fullfill their business strategies . This paper discuss es IT governance in general based on the literature study, how it can help the top management to manage their IT dan policies that conform to the ir business strategies. The findings suggest that IT is expensive, leading to questions concerning the benefits of IT investment and the importance of IT in business context. These questions challenge the CEOs to be strategic partner for business.Â Keywords: IT governance, CIO, maturity